To solve this equation, we will distribute the 2 to each term inside the parentheses:
2(1.5x − 7) = 6
2 * 1.5x - 2 * 7 = 6
3x - 14 = 6
Next, we will isolate the variable x by moving the constant term (14) to the other side of the equation:
3x = 6 + 14
3x = 20
Finally, we can solve for x by dividing both sides of the equation by 3:
x = 20/3 or x = 6.67
2(1.5x−7)=6
7 answers
5x - 2x + 4 = -5
To solve this equation, we will first combine like terms on the left side of the equation:
5x - 2x + 4 = -5
(5x - 2x) + 4 = -5
3x + 4 = -5
Next, we will isolate the variable x by moving the constant term (4) to the other side of the equation:
3x = -5 - 4
3x = -9
Finally, we can solve for x by dividing both sides of the equation by 3:
x = -9/3
x = -3
5x - 2x + 4 = -5
(5x - 2x) + 4 = -5
3x + 4 = -5
Next, we will isolate the variable x by moving the constant term (4) to the other side of the equation:
3x = -5 - 4
3x = -9
Finally, we can solve for x by dividing both sides of the equation by 3:
x = -9/3
x = -3
9x + 9x - 21 = 33
To solve this equation, we will first combine like terms on the left side of the equation:
9x + 9x - 21 = 33
(9x + 9x) - 21 = 33
18x - 21 = 33
Next, we will isolate the variable x by moving the constant term (-21) to the other side of the equation:
18x = 33 + 21
18x = 54
Finally, we can solve for x by dividing both sides of the equation by 18:
x = 54/18
x = 3
9x + 9x - 21 = 33
(9x + 9x) - 21 = 33
18x - 21 = 33
Next, we will isolate the variable x by moving the constant term (-21) to the other side of the equation:
18x = 33 + 21
18x = 54
Finally, we can solve for x by dividing both sides of the equation by 18:
x = 54/18
x = 3
14x - 3x + 11= -22
To solve this equation, we will first combine like terms on the left side of the equation:
14x - 3x + 11 = -22
(14x - 3x) + 11 = -22
11x + 11 = -22
Next, we will isolate the variable x by moving the constant term (11) to the other side of the equation:
11x = -22 - 11
11x = -33
Finally, we can solve for x by dividing both sides of the equation by 11:
x = -33/11
x = -3
14x - 3x + 11 = -22
(14x - 3x) + 11 = -22
11x + 11 = -22
Next, we will isolate the variable x by moving the constant term (11) to the other side of the equation:
11x = -22 - 11
11x = -33
Finally, we can solve for x by dividing both sides of the equation by 11:
x = -33/11
x = -3